2016
DOI: 10.1158/0008-5472.can-15-1115
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP1 Selectively Destabilizes Transcripts Associated with an Antiapoptotic Gene Expression Program in Breast Cancer Cells That Can Elicit Complete Tumor Regression

Abstract: The ability of cancer cells to evade apoptosis is dictated by a shift in the balance between pro- and anti-apoptotic gene expression programs. Monocyte chemotactic protein induced protein 1 (MCPIP1) is a zinc finger RNA binding protein with important roles in mediating inflammatory responses. Overexpression of MCPIP1 in different cancer cell types has been implicated in eliciting an antitumor response, but a direct role of MCPIP1 in apoptosis has not been established. In this study, we demonstrate that MCPIP1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
105
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(109 citation statements)
references
References 47 publications
2
105
2
Order By: Relevance
“…In our models, low MCPIP1 levels significantly increased the cell proliferation, tumor growth, and tumor weight of ccRCC. In contrast, MCPIP1 overexpression decreases the proliferation in vitro and reduced tumor growth in vivo as it was demonstrated for breast cancer (22). Interestingly, the analysis of tumors generated by cells carrying a point mutation of D141 (D141N) that completely abolishes MCPIP1 RNase activity (13) demonstrated that the loss of endoribonuclase activity of MCPIP1 significantly increased tumor growth in both investigated models.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In our models, low MCPIP1 levels significantly increased the cell proliferation, tumor growth, and tumor weight of ccRCC. In contrast, MCPIP1 overexpression decreases the proliferation in vitro and reduced tumor growth in vivo as it was demonstrated for breast cancer (22). Interestingly, the analysis of tumors generated by cells carrying a point mutation of D141 (D141N) that completely abolishes MCPIP1 RNase activity (13) demonstrated that the loss of endoribonuclase activity of MCPIP1 significantly increased tumor growth in both investigated models.…”
Section: Discussionmentioning
confidence: 90%
“…It has been already demonstrated that MCPIP1 regulates the viability and proliferation of neuroblastoma (20), HeLa, HepG2 (19), ccRCC (25), and breast cancer cells (21). Previous findings have demonstrated that MCPIP1 degrades the mRNA of antiapoptotic gene transcripts in breast cancer cells, leading to apoptosis and tumor regression (22). Moreover, the same study showed that MCPIP1 expression in breast cancer samples was reduced compared with that in healthy tissue, and low MCPIP1 expression was associated with tumor progression and poor survival (22).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The main physiological function of the protein is negative regulation of inflammation [Jura et al, 2012]. Roles of MCPIP1 in differentiation and apoptosis have also been described in mesenchymal stem cells and breast cancer [Labedz-Maslowska et al, 2015;Lu et al, 2016].…”
mentioning
confidence: 99%